Implementasi Bimbingan Mengaji dengan Metode Yanbu’a sebagai Upaya Pembentukan Karakter Religiusitas pada Anak TPQ As-Sidiq Desa Talang Sebaris - Adrian Topano; Indah Oktaviani; Novita Kemala Dewi; Shella Pironica; Deva Surya Firdaus; Robi Riyansyah; Lidya Damayanti (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Religious education and character education are two related concepts. In its application, Al-Quran teaching plays a very important role in shaping children's character through guidance, continuous education and advice to instill religious, independent and communicative qualities in them from an early age. The aim of this research is to develop the implementation of religious character in higher education religious activities. The research methodology used is qualitative. With religious education that teaches the art of reading the Koran and its translations, the role of Taman Al-Coran (TPQ) is very important in forming the character of babies from an early age. Apart from that, there are other religious practices, such as memorizing short poetry and daily prayers, which can indirectly provide Islamic life lessons. However, a child's character must also be shaped and guided by his family so that he grows into a good person. The application of religious character in religious activities takes the form of participation in what are called